Jejak Kaum Sayyid dalam Pribumisasi Islam di Dieng - Ahmad Hidayatullah (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2022)
Dieng has a long history until it finally became an area with the majority of the population being Muslim, even understanding Ahlussunnah wal Jama'ah. This cannot be separated from the process of indigenizing Islam in the Dieng plateau by the Sayyids – which is an extension of Walisongo's struggle. Using this type of qualitative research with a critical-historical discourse analysis approach (Discourse-Historica Approaches/DHA), this study tries to explore how the indigenization of Islam was carried out by the Sayyids in the Dieng plateau. As for the results of this study, it can be concluded that based on the evidence contained in the grave sites and remains of the Sayyids; Sheikh Karim, Sheikh Ngabdullah Selomanik, Sheikh Adam Sari, it is said that they did the indigenization of Islam in Dieng in the XVI-XVII centuries. The strategy and understanding that has been disseminated to the community is what Walisongo has done, namely a cultural approach that compromises the meeting of culture and sharia as one thing that does not need to be contradicted, and instead collaborates. Then ideologically, the ideology that was spread was the understanding of Ahlusunnah wal Jamaah which is still believed and practiced by the Muslim community in Dieng.